In sloot en plas - Heimans, Eli, 1861-1914; Thijsse, Jac. P. (Jacobus Pieter), 1865-1945 (Salt Lake City, UT : Project Gutenberg, 2022)
"In sloot en plas" by Eli Heimans and Jac. P. Thijsse is a nature guide published in 1895. Part of the pioneering series "Van vlinders, bloemen en vogels," this work introduces readers to the living communities found in ditches and ponds. The authors explore how plants and animals exist together in interconnected ecosystems, presenting nature observations through fresh writing and original illustrations. Aimed initially at young readers, the book became beloved by adults too, earning nine editions over sixty-five years. (This is an automatically generated summary.)
Illustrated by the authors.
Wikipedia page about this book: https://nl.wikipedia.org/wiki/Van_vlinders,_bloemen_en_vogels
Release date is 2022-10-16
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg
Keywords: Natural history -- Netherlands; Freshwater animals; Freshwater plants